Coastal Wetlands Drive Isotopic Niche Plasticity of Top Predator Fish Communities in Green Bay, Lake Michigan (USA) - Tania V. Rojas; Katherine E. O'Reilly; Christopher J. Houghton; Jeremiah S. Shrovnal; Martin B. Berg; Donald G. Uzarski; Gary A. Lamberti; Patrick S. Forsythe (Ecology and Evolution)
ABSTRACT Green Bay, the largest freshwater embayment in Lake Michigan, is a unique environment consisting of a trophic gradient along its north‐to‐south axis that shapes the heterogeneous and dynamic habitat, driving diverse fish behavior among the remnant coastal wetlands of Green Bay. Although previous studies of aquatic food webs in Green Bay have focused on lower trophic levels to estimate trophic shift responses, we examined trophic relationships among fish communities in five coastal wetland areas of Green Bay, emphasizing top predator species of recreational and commercial importance in Lake Michigan. We used stable isotope‐based community metrics and Bayesian mixing models to describe food web structure and patterns in trophic position, isotopic niche, and diet contributions of top predators, including bowfin Amia calva, largemouth bass Micropterus salmoides, northern pike Esox lucius, smallmouth bass Micropterus dolomieu, walleye Sander vitreus, and yellow perch Perca flavescens. We found high probability (> 70%) of overlap among the isotopic niches of piscivorous, invertivorous, and benthivorous fish, reflecting the capacity of different feeding guilds to exploit isotopically similar sources. In addition, we found that invertivorous fish represented a critical trophic link between the top‐level fish populations and lower levels, such as aquatic invertebrates. Lastly, we found that top predators diversified their diet in lacustrine wetlands but had a distinct foraging habitat preference in riverine wetlands, emphasizing the importance of habitat type and structure in feeding diversity. Top predators in Green Bay displayed a high degree of isotopic niche plasticity, as evidenced by differences in trophic positions and foraging strategies at each site. Flexibility in fish feeding ecology, such as variations in dietary overlap and niche space, along with the hydrogeomorphic setting, underpins the ability of fish communities of Green Bay to thrive under different stressors.